Collaborating With Businesses to Support and Sustain Research. (October 2015) - Moch, Susan Diemert; Jansen, Debra A.; Jadack, Rosemary A.; Page, Phil; Topp, Robert
Financial assistance is necessary for sustaining research at universities. Business collaborations are a potential means for obtaining these funds. To secure funding, understanding the process for obtaining these business funds is important for nursing faculty members. Although faculty rarely request funding from businesses, they are often in a position to solicit financial support due to existing relationships with clinical agency administrators, staff, and community leaders. The economic support received from businesses provides outcomes in nursing research, research education, academic–service partnerships, and client health care. This article describes the steps and processes involved in successfully obtaining research funding from businesses. In addition, case examples for securing and maintaining funding from health care agencies (evidence-based practice services) and from a health manufacturing company (product evaluation) are used to demonstrate the process.